Global Health Solidarity: A Multidimensional Framework - Wang, Yijie (Bioethics, 2026)
Solidarity has emerged as a vital concept in bioethics. In recent years, the concept of solidarity has transcended domestic boundaries, with its rhetorical power being leveraged across diverse global health contexts. However, despite its prominence in bioethics and its rhetorical use in global health, health solidarity remains largely confined to domestic contexts. This paper fills this gap by exploring the possibility of extending health solidarity on a global level. Rather than pursuing a singular, unitary concept, I propose to conceptualize global health solidarity (GHS) with a multidimensional framework that encompasses four essential modes: prudential, moral, sociopolitical, and institutional. The prudential mode provides a compelling foundation for GHS through self-interested motivations, emphasizing global health interdependence. The moral mode frames GHS as morally right or good, grounded in relational personhood, functioning either as a duty or a virtue. The sociopolitical mode conceptualizes GHS as a politically significant, prosocial phenomenon in pursuing liberation and confronting injustices, enabling project-based collaboration beyond identity boundaries. The institutional mode formalizes GHS through established structures, shaping global bioethics frameworks and health governance systems. Recognizing these diverse sources, contexts, and practices of solidarity, the multidimensional framework offers a comprehensive conceptual map for understanding and operationalizing GHS. It provides both analytical clarity and practical guidance for navigating solidarity-based practices in global health contexts. When compared with established frameworks, such as global health justice, global health governance, global health activism, and global health security, GHS provides distinct added value and deserves a more fundamental place in the current global health discourse.